2018
DOI: 10.1111/apa.14497
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics promoted head growth in extremely low birthweight infants in a double‐blind placebo‐controlled trial

Abstract: Lactobacillus reuteri did not reduce time to reach full enteral feeds in ELBW infants. The L. reuteri supplemented infants, however, had a better growth rate of the head during the first month of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 30 publications
2
63
1
Order By: Relevance
“…The present study was a part of the prospective, randomized-controlled, multi-centre trial “Prophylactic Probiotics to Extremely Low Birth Weight Premature Infants” (PROPEL) evaluating the effect of probiotic Lactobacillus reuteri DSM 17938 on feeding tolerance, growth, severe morbidities, and mortality in ELBW premature infants (ClinicalTrials.gov ID NCT01603368). A detailed study design and the clinical outcomes have been published elsewhere [ 21 ]. Briefly, in total 134 infants born between gestational week (gw) 23 + 0 and 27 + 6 with a birth weight below 1000 g were enrolled between 2012 and 2015 at two level III neonatal intensive care units (Astrid Lindgren Children’s Hospital, Stockholm, and Linköping University Hospital, Linköping, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…The present study was a part of the prospective, randomized-controlled, multi-centre trial “Prophylactic Probiotics to Extremely Low Birth Weight Premature Infants” (PROPEL) evaluating the effect of probiotic Lactobacillus reuteri DSM 17938 on feeding tolerance, growth, severe morbidities, and mortality in ELBW premature infants (ClinicalTrials.gov ID NCT01603368). A detailed study design and the clinical outcomes have been published elsewhere [ 21 ]. Briefly, in total 134 infants born between gestational week (gw) 23 + 0 and 27 + 6 with a birth weight below 1000 g were enrolled between 2012 and 2015 at two level III neonatal intensive care units (Astrid Lindgren Children’s Hospital, Stockholm, and Linköping University Hospital, Linköping, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…The present study was a part of the prospective, double-blinded, randomized controlled multicenter trial Prophylactic Probiotics to Extremely Low Birth Weight Premature Infants, evaluating the effect of probiotic L. reuteri DSM 17938 on feeding tolerance, growth, severe morbidities, and mortality in ELBW premature infants (http://clinicaltrials.gov, identifier: NCT01603368). The study design has been described in detail elsewhere (22). Briefly, 134 ELBW infants were supplemented either with the probiotic bacterial strain L. reuteri DSM 17938 or placebo.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…gave 134 extremely low‐birthweight infant oil drops containing the probiotic Lactobacillus reuteri DSM 17938 or a placebo. They did this once a day until the infants reached 36 weeks of gestation . The authors found that the probiotic did not reduce the time it took the infants to reach full enteral feeds.…”
Section: Probiotics Promoted Head Growth In Extremely Low‐birthweightmentioning
confidence: 99%